La profesión legal y la tecnología en el Perú - Montezuma Panez, Óscar (2021)
ADVOCATUS had the opportunity to interview Óscar Montezuma Panez, Peruvian digital lawyer specialized in Technology Law, intelectual property, Competition Law, digital businesses and legal innovation. In the following lines he offers his opinions about the legal profession and its relationship with technology in Peru, addressing issues such as the use of social media and software, the formalities of Law and reflections on innovation.